Recognizing the Sequences of Code Manipulated Short LFM Signals - LESZCZYŃSKI, Tadeusz (Archives of Acoustics, 2012)
Noise-like binary sequences combined with signals with linear frequency modulation might be suc-cessfully used to increase the reliability of the recognition of both probe and communication signals inthe presence of natural and artificial interference. To identify such formed sequences the usage of thetwo-step matched filtering was suggested and the probabilistic model of the recognition of noise-like codesequences transferred by LFM signals was developed.